Engaging Vocational High School Students In Word Mapping Strategy In Learning Technical Vocabulary: A Classroom Action Research - Rainsyah, Raihana Marsha; Yanto, Elih Sutisna; Fitriyana, Wahyudin (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study reports the results of vocational high school students' use of a word map graphic organizer and YouTube as digital media for learning the technical vocabulary of procedure texts. This paper utilized a classroom action research design, in which the researcher plays an active role in the classroom and collects data through semi-structured interviews and documentation. The majority of students enjoyed and were interested in learning technical vocabulary using word map graphic organizers and digital procedure text videos, as determined through thematic analysis of empirical data. Through the use of a word map graphic organizer, students were encouraged to uncover and evaluate technical vocabulary knowledge in the digital procedure text video. Nevertheless, some students found it difficult to utilize the word map graphic organizer in the word mapping strategy.